WAYS TO MAKE HIGHER EDUCATION BETTER IN INDONESIA BY IMPROVING LECTURER PERFORMANCE - Harliantara Harliantara (Universitas Islam Sultan Agung, 2025)
Indonesia must improve its higher education so graduates may benefit society and the economy. It looks at how well lecturers do their jobs, which is an important part of the total quality of education. This study did a literature review on higher education in Indonesia using a qualitative method. This shows how important it is to provide regular professional development, make a thorough method for evaluating performance, enhance infrastructure and resources, encourage partnerships within the industry, and set up mentoring programs. The study also shows how important it is to know how to use technology, how to teach online, how to work with people from different fields, and how to have clear job paths. To help lecturers do a better job, it is important to encourage new ways of teaching, set up useful feedback systems, and ensure there is enough staff support. The study's conclusion is that attempts to improve the performance of lecturers can make higher education in Indonesia better. The people who make decisions and run schools need to know these results if they want to make Indonesian higher education more competitive and relevant to the global knowledge economy.